AKTIVITAS ENZIM ALKALIN FOSFATASE (ALP) PADA SERUM DARAH ITIK TEGAL (Anas platyrhynchos) - , DWI KRISTANTO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The aim of this study was to find out the ratio of Alkaline Phosphatase (ALP) enzyme activity on blood serum between drakes and laying Tegal ducks. Twelve clinically healthy Tegal ducks, which were divided into 6 drakes and 6 laying ducks, were used in this study. Blood samples were collected through brachialis vein. Obtained samples were centrifuged at 8000 rpm for 8 min. Serum was analysed using Alkaline Phosphatase Assay Kit test method and was measured by spectrophotometer. The data was analyzed statistically using t-test method to compare 2 data populations